CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

The solution of the equation $$\sqrt{x^2-16}-(x-4)=\sqrt{x^2-5x+4}$$ is?


A
{4,5,133}
loader
B
{4,5}
loader
C
{4}
loader
D
{5,133}
loader

Solution

The correct option is A $$\left\{4, 5, -\dfrac{13}{3}\right\}$$
$$\quad \sqrt{(x-4)(x+4)-(x-4)}=\sqrt{(x-4)(x-1)}$$
$$\Rightarrow \sqrt{(x-4)}\{\sqrt{x+4}-\sqrt{x-4}\}=\sqrt{(x-4)} \times \sqrt{(x-1)}$$
$$\Rightarrow \sqrt{x-4}=0 \quad \Rightarrow \quad x=4$$
or 
$$\sqrt{x+4}-\sqrt{x-4}=\sqrt{x-1}$$
Squaring both sides,
$$x+4+(x-4)-2 \sqrt{x^{2}-16}=x-1$$
$$\Rightarrow x+1=2 \sqrt{x^{2}-16}$$
Squaring both sides we get
$$\Rightarrow 3 x^{2}-2 x-65=0$$
$$\Rightarrow x=5, \dfrac{-13}{3}$$
$$\therefore x=\left\{5,4,-\dfrac{13}{3}\right\}$$
option $$A$$ is correct.

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More



footer-image